2012
DOI: 10.1007/s00428-012-1319-7
|View full text |Cite
|
Sign up to set email alerts
|

Serrated polyps of the colon: how reproducible is their classification?

Abstract: For several years, the lack of consensus on definition, nomenclature, natural history, and biology of serrated polyps (SPs) of the colon has created considerable confusion among pathologists. According to the latest WHO classification, the family of SPs comprises hyperplastic polyps (HPs), sessile serrated adenomas/polyps (SSA/Ps), and traditional serrated adenomas (TSAs). The term SSA/P with dysplasia has replaced the category of mixed hyperplastic/adenomatous polyps (MPs). The present study aimed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 32 publications
2
73
0
Order By: Relevance
“…This led to a position paper by the American Society of Gastrointestinal Endoscopy (ASGE), which set two preconditions for such an approach,12 namely, required accuracy in the prediction of post-polypectomy surveillance intervals of more than 90% and required negative predictive value for adenomatous histology of 90% or more. The recently introduced topic of serrated adenomas and their differential diagnosis in comparison to hyperplastic polyps with still substantial inter-observer variability on histopathological analysis complicates this issue further and does not support a significant role of endoscopic imaging at present because histopathological inter-observer agreement is already rather limited 22. A limitation of our study may therefore be that no uniform histopathology is available.…”
Section: Discussionmentioning
confidence: 85%
“…This led to a position paper by the American Society of Gastrointestinal Endoscopy (ASGE), which set two preconditions for such an approach,12 namely, required accuracy in the prediction of post-polypectomy surveillance intervals of more than 90% and required negative predictive value for adenomatous histology of 90% or more. The recently introduced topic of serrated adenomas and their differential diagnosis in comparison to hyperplastic polyps with still substantial inter-observer variability on histopathological analysis complicates this issue further and does not support a significant role of endoscopic imaging at present because histopathological inter-observer agreement is already rather limited 22. A limitation of our study may therefore be that no uniform histopathology is available.…”
Section: Discussionmentioning
confidence: 85%
“…Of the SSA subtypes, concordance was 100 % for SSA and 90 % for pSSA, defined as below the WHO definition threshold for SSA-type crypt number [27]. In contrast, two further studies on interobserver agreement found rather disappointing results [13,14].…”
Section: Discussionmentioning
confidence: 93%
“…With regards to their relative distribution within the group of serrated lesions, the rise of SSA detection rate over time [10] could be at least partially due to a shift in diagnosis from hyperplastic polyps on histopathological review [11,12]. The distinction between SSA and HP, however, may be difficult, and previous studies have also reported poor to fair interobserver agreement rates for histopathological diagnosis of SSA versus HP, with kappa values ranging from 0.16 to 0.38 [11,13,14]. For these reasons, diagnostic criteria for SSA have been recently refined by several expert panels and consensus conferences [2,15], in the hope of arriving at a more uniform and reproducible histopathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This has been reported in serrated lesion classification, however all cases were reviewed by subspecialty GI pathologists and with the release of the updated 2010 WHO guidelines recent studies have shown very good reproducibility among pathologists 41. Molecular studies were not performed to document underlying serrated pathway mutations, hence SSA/P-D with conventional adenomatous morphology and without residual SSA/P that were endoscopically and pathologically assessed to be conventional adenomas may have been missed.…”
Section: Discussionmentioning
confidence: 99%